2012
DOI: 10.1111/myc.12020
|View full text |Cite
|
Sign up to set email alerts
|

Erythema nodosum induced by kerion celsi of the scalp in a child: a case report and mini‐review of literature

Abstract: A 9-year-old girl, presented with a 4-week history of an inflammatory suppurative plaque, 8 cm in diameter, localised in the occipital area of the scalp. Mycological direct examination showed ectoendothrix invasion of the hair and Trichophyton mentagrophytes was isolated. Oral therapy with griseofulvin 25 mg kg(-1)  day(-1) was prescribed, but after 2 weeks of treatment appeared multiple erythematous subcutaneous nodules localised in the legs. Erythema nodosum (EN) was confirmed by histological examination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Id reactions tend to occur at the height of the dermatophyte infection, slightly thereafter, or before or just after the initiation of systemic antifungal therapy, which can vary from 5 to 20 days (6,7,9,12). Cheng et al (12) and Castriota et al (17) reported that dermatophytid reactions appeared after systemic antifungal therapy. In our study, all dermatophytid reactions were determined at the initial visit, before treatment was begun.…”
Section: Discussionmentioning
confidence: 99%
“…Id reactions tend to occur at the height of the dermatophyte infection, slightly thereafter, or before or just after the initiation of systemic antifungal therapy, which can vary from 5 to 20 days (6,7,9,12). Cheng et al (12) and Castriota et al (17) reported that dermatophytid reactions appeared after systemic antifungal therapy. In our study, all dermatophytid reactions were determined at the initial visit, before treatment was begun.…”
Section: Discussionmentioning
confidence: 99%
“…Criteria for the diagnosis of a dermatophytid include: (1) evidence of a (frequently) inflammatory dermatophytosis at another site of the body (here, TC); (2) no evidence of fungal elements in the dermatophytid lesions; (3) initially, there is frequently a clinical flare-up upon starting highly effective systemic antifungal therapy (release of large amounts of fungal antigens). Dermatophytid reactions reported to be associated with TC include: symmetrically disseminated papular or papulovesicular eczematous lichenoid lesions with follicular accentuation that usually develop on the trunk (lichen trichophyticus); erythema nodosum and erysipelas-like dermatitis; psoriasiform lesions; erythema multiforme; urticarial and erythema annulare centrifugum-like lesions [37,38,[41][42][43][44]. While dermatophytids usually occur on the trunk, extremities and face, generalized eruptions are also possible.…”
Section: Infection Patterns and Clinical Presentationmentioning
confidence: 99%
“…While dermatophytids usually occur on the trunk, extremities and face, generalized eruptions are also possible. Dermatophytid reactions reported to be associated with TC include: symmetrically disseminated papular or papulovesicular eczematous lichenoid lesions with follicular accentuation that usually develop on the trunk (lichen trichophyticus); erythema nodosum and erysipelas-like dermatitis; psoriasiform lesions; erythema multiforme; urticarial and erythema annulare centrifugum-like lesions [37,38,[41][42][43][44].…”
Section: Infection Patterns and Clinical Presentationmentioning
confidence: 99%
“…These patients have a strong delayed-type hypersensitivity [DTH] reaction to intradermal trichophytin. EN is thought to be due either the deposition of immune complexes in capillaries and venules of the dermal and adipose plexus, or to a DTH reaction to an antigen [55,56].…”
Section: Kerion Celsi [Kc] [So-called Deep Tinea Capitis] Is An Uncommentioning
confidence: 99%